2010
DOI: 10.1111/j.1432-2277.2010.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care staffs’ attitudes, confidence levels and educational needs correlate with countries’ donation rates: data from the Donor Action® database

Abstract: Summary To investigate on the impact of Critical Care (CC) staffs’ attitudes to donation, their acceptance of the brain death (BD) concept, their confidence with donation‐related tasks and educational needs on national donation rates. Donor Action (DA) Hospital Attitude Survey (HAS) data were collected from 19 537 CC staff in 11 countries, including personal attitudes to donation, self‐reported knowledge, involvement and comfort levels with donation‐related tasks and educational requirements. Countries’ donati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 35 publications
3
50
2
5
Order By: Relevance
“…The learning needs were associated with deficiencies in terms of skills and experience. Another study from a Norwegian intensive-care unit in which considerable attention had been devoted to organ donation showed that the doctors were very confident about their own abilities in this area (6). Our findings indicate that this is not representative of Norwegian doctors in general.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The learning needs were associated with deficiencies in terms of skills and experience. Another study from a Norwegian intensive-care unit in which considerable attention had been devoted to organ donation showed that the doctors were very confident about their own abilities in this area (6). Our findings indicate that this is not representative of Norwegian doctors in general.…”
Section: Discussioncontrasting
confidence: 52%
“…The doctors' knowledge about organ donation, attitude to it and ability to relate to the potential organ donor and his or her next of kin may be decisive for obtaining consent to an organ donation (2)(3)(4)(5)(6)(7). A review article published in 2009 (5) showed that specific skills in the person who provides information and inquires, as well as the timing of the inquiry, may have a greater effect on the likelihood that the next of kin will provide consent for an organ donation than legislation and regulations.…”
mentioning
confidence: 99%
“…En la tabla 2, se evidencia que los conocimientos sobre donación de órganos y tejidos para el pre y post test son estadísticamente de distribución normal por ser mayores a 0.05; según lo encontrado, guarda relación con los estudios realizados por Roels L, Spaight C, Smits J. y Cohen B., al lograr los objetivos en su investigación donde precisan que, para corregir el rendimiento de la donación de los países debe centrarse en la educación a fin de garantizar que exista el suficiente conocimiento respecto a la donación de órganos y tejidos, concluyendo, que al educar a los médicos y enfermeras sobre los criterios para la donación de órganos y tejidos y subrayando su papel en la toma de la solicitud, han dado lugar a aumentos medibles en la donación (12). Relacionando al estudio propone que se brinde la información actualizada por personal capacitado durante las intervenciones educativas Del mismo modo, según Vargas E. al adaptar uno de los supuestos de la teorista Pender N, al tema, se obtiene "Los adultos de 20 a 40 años buscaran crear condiciones de vida con los conocimientos adoptados mediante las intervenciones educativas de Enfermería las cuales puedan pronunciar su conformidad de ser un potencial donador de órganos y tejidos para preservar la salud humana (13), lo que coincide con los resultados entre el pre test y post test respectivamente.…”
Section: Discussionunclassified
“…El instrumento, es elaborado y aplicado por la investigadora,consta de cuatro segmentos: introducción, instructivo, datos usuales y 14 ítems que los adultos contestarán de acuerdo a sus realidades referentes a la donación de órganos y tejidos; se han considerado para la dimensión 1, Generalidades 6 ítems (1,2,3,4,5,6); para la dimensión 2, Procedimientos 4 ítems (7,8,9,10) y dimensión 3, Aspecto legal, 4 ítems (11,12,13,14). Realizando su aplicación en un solo momento utilizando la entrevista personal a los individuos en forma particular y en grupos de dos a tres personas respectivamente; el tiempo empleado fue de 30 minutos (anexo 9).…”
Section: Tejidos (Ecdo)unclassified
“…The technical solution lies in lowering these refusal rates (e.g. Dunkel 2011;Roels et al 2010;Shafer et al 2006;Simillis 2010;Simpkin et al 2009). Figure 2 illustrates that implementing agents who put policy instruments "on paper" into practice may adapt these instruments (Lipsky 1980(Lipsky /2010.…”
Section: Measuring Explicitnessmentioning
confidence: 99%